A study for the influences of temperatures on ZnGa2O4 films and solar-blind sensing performances. (28th July 2021) - Lu, Chengling; Zhang, Qingyi; Li, Shan; Yan, Zuyong; Liu, Zeng; Li, Peigang; Tang, Weihua
Abstract: In this work, ZnGa2 O4 metal–semiconductor–metal solar-blind ultraviolet (UV) photodetectors were fabricated and discussed by using the radio-frequency (r.f.) magnetron sputtering method with considerations of the influences of growing and measuring temperatures on photoelectric performances in detail. With the increase of growing temperature, the grain size and optical bandgap of the films increased. Ohmic contacts were formed between the films and Ti/Au electrodes for all the samples, and the photoconductive photodetectors shown decent solar-blind photoelectric performances. At 10 V biasing voltage, the devices had fast response speed and large photo-to-dark current ratio of ∼10 7 at 650 °C. Moreover, we measured the dark current ( I dark ) and photocurrent ( I photo ) of these devices in the temperature range from 298 K to 598 K. With the increase of temperature, the I dark increased monotonously, while the I photo first decreased and then increased. Furthermore, this study about the effects of temperatures on the ZnGa2 O4 films and photodetectors may well provide a meaningful guide for its relevant developments in the future.